Peran Guru Pendidikan Agama Katolik dalam Meningkatkan Motivasi Belajar Peserta Didik Kelas XI IPS di SMA Swasta RK Serdang Murni Lubuk Pakam - Sembiring, Veronika; Sembiring, Mimpin (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study aims to explore the role of Catholic Religious Education Teachers in increasing students' learning motivation in Private High School RK Serdang Murni Lubuk Pakam. This study uses a qualitative descriptive method with a qualitative approach. A total of 12 informants consisting of students, Catholic Religious Education teachers, and school principals were involved in this study. Data collection is done through observation, interviews, and documentation. The results of data processing show two main things. First, there was an increase in learning motivation in class XI IPS students at RK Serdang Murni Lubuk Pakam Private High School. Second, the role of the Catholic Religious Education Teacher is very important and influential in increasing student learning motivation. Based on the results of this study, it is recommended that Catholic Religious Education Teachers continue to play an active role in increasing the learning motivation of class XI IPS students at the Private High School RK Serdang Murni Lubuk Pakam, and continue to use the same approach in dealing with these students.